Pattern of Lumbar MRI Changes in Patients with Chronic Low Back Pain in a Tertiary Care Center - Sharma, Rupesh; Tiwari, Awadhesh; Dwivedi, Rajeev (Journal of Lumbini Medical College, 2018)
Introduction: Chronic low back pain (LBP) is a common cause of disability worldwide. Magnetic resonance imaging (MRI) is an excellent non-invasive imaging modality for morphologic evaluation of the lumbar spine in patients with chronic low back pain because of its high contrast resolution and lack of ionizing radiation. This study was done to see the patterns of MRI changes in patients with chronic low back pain in a tertiary care center in Western Nepal. Methods: This was a cross-sectional study conducted on patients presenting with chronic low back pain. Eleven MRI parameters were noted and analyzed. Chi square test and Fisher’s Exact test were employed to see the associations between the various MRI findings. Results: A total of 108 patients were evaluated during the study period. MRI changes were noted in over 95% of the cases. Degenerative changes were the most common cause of low back pain, disc bulge being the most common MRI finding. A significant association was found between radiculopathy and decreased lumbar lordosis and vertebral endplate changes. Conclusion: MRI is an invaluable tool in the evaluation of chronic LBP because of its high resolution and lack of ionizing radiation. Significant MRI findings are noted in most of the cases of chronic LBP, degenerative changes being the most common and ranging from congenital to malignant lesions. DOI: https://doi.org/10.22502/jlmc.v6i2.273